UPAYA MENINGKATKAN AKHLAKUL KARIMAH DALAM PELAKSANAAN PENDIDIKAN AGAMA ISLAM DI SMPN I PAJARAKAN - Ilyas, Muhammad (Humanistika : Jurnal Keislaman, 2016)
Religious Education is an integral of National Education. Therefore the conduct of Islamic education absolutely must be effective and efficient in order to achieve specific objectives in improving akhlakul Karimah in SMP Negeri I Pajarakan .Students in the SMPN I Pajarakan constitute the majority of personal development has not yet reached maturity, still not able to control the behavior that is expected. Based on this background problems arise among them how the implementation of Islamic religious education in improving akhlakul karimah, what is being done to improve akhlakul karimah, any factors that support and hinder the increase akhlakul karimah. To the authors try to express through this study to determine the effectiveness of the implementation of Islamic religious education in relation to improving akhlakul karimah and to determine the factors that become supporters and obstacles in the implementation of the increase akhlakul karimah.For data collection method the authors use methods include: observation, interview and documentation. The type of research is qualitative. Data were analyzed using qualitative description of data that researchers use data descriptions in the form of words written or oral, and behaviors of people who can be observed.